A Randomized, Double‐Blind, Crossover Study to Evaluate the Depth Response Relationship of Intradermal Capsaicin‐Induced Pain and Hyperalgesia in Healthy Adult Volunteers. Issue 4 (19th December 2014) - Silberberg, Alan; Moeller‐Bertram, Tobias; Wallace, Mark S.
Abstract Objective The purpose of this study was to evaluate pain and hyperalgesia in response to different depths of intradermal (ID) capsaicin injections in healthy volunteers. Design Double‐blind, cross‐over study. Setting Clinical Research Laboratory. Subjects Fifteen healthy male subjects received ID capsaicin injections into the volar aspect of each forearm at depths of 1 mm, 3 mm, 5 mm, and 7 mm. After injection, spontaneous pain, elicited pain, flare response, heat thresholds, and area of hyperalgesia were measured at various time points. Outcomes Measure Spontaneous pain, elicited pain (pinprick, stroking, and hot pain), hyperalgesia area, and allodynia area. Results No significant difference was found between any depths in spontaneous pain, elicited pain (pinprick, stroking, hot pain), hyperalgesia area, or allodynia area. A significant difference was found in the change in heat threshold between 5 mm and 1 mm, 7 mm and 1 mm, 5 mm and 3 mm, 7 mm and 3 mm depths. A significant difference was found in flare area between 5 mm and 3 mm depths. A significant difference was found in systolic blood pressure area under the curve (AUC) between 7 mm and 1 mm depths, and for both systolic and diastolic pressures for 5 mm and 1 mm depths, and 5 mm and 3 mm depths. A significant difference was found in pulse AUC between 5 mm and 1 mm depths and 5 mm and 3 mm depths. Conclusions Injection of capsaicin at different depths in the skin had different effects on heart rate and blood pressure but no effect on pain. These results may have implications on the pharmacology and analgesic predictive value of the model of ID capsaicin.